A taxonomy of seven‐day readmissions to an urban teaching hospital. Issue 1 (23rd September 2015) - Burke, Daniel; Link, Nate; Bails, Douglas; Fang, Yixin; Janjigian, Michael P.
Abstract : BACKGROUND: Understanding the mechanism of unplanned hospital readmissions is necessary for accurate prediction and prevention. OBJECTIVE: To identify specific mechanisms of unplanned readmissions through medical narratives obtained from chart reviews. DESIGN: Retrospective chart review. SETTING: Urban tertiary care hospital. PATIENTS: Two hundred seventy patients accounted for 335 unplanned 7‐day readmissions between July 2010 and July 2011. MEASUREMENTS: Readmissions were classified into 1 of 5 distinct categories. RESULTS: Readmitted subjects were more likely to have had a longer length of stay during the first admission compared to nonreadmitted patients. Readmissions due to unpredictable/unpreventable complications or unrelated events constituted the highest percentage at 46%. Readmissions due to patient factors such as substance abuse, signing out against medical advice, or nonadherence to the treatment plan constituted 31%. Readmissions designated as preventable accounted for 24%. Among preventable readmissions, the most common cause was incomplete management of the index diagnosis. The interobserver level of agreement across the 5 major categories was substantial. CONCLUSIONS: We found through detailed chart review of patients readmitted within 7 days to an urban teaching hospital that the majority of readmissions were not avoidable and were often due to unpredictable or unpreventable complications of the primary diagnosis from the index hospitalization or to patient behaviors that contradicted the treatment plan. These results question the value of readmissions as a valid metric of quality and support future interventions in hospital systems to reduce preventable readmissions. Journal of Hospital Medicine 2016;11:33–38. © 2015 Society of Hospital Medicine